Analisis Nilai Perusahaan Ditinjau dari Kinerja Keuangan, Firm Size, Struktur Modal pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Siska Indriyani; Istiatin; Ratna Damayanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research is a type of quantitative descriptive research. The population used as the subject is all companies in the transportation and logistics sector that are listed on the Indonesia Stock Exchange in the 2019-2021 period, a total of 30 companies. The sampling method for this study used purposive sampling, which resulted in 15 companies as samples, with a total of 45 observational data. In the analysis, researchers used multiple regression methods using SPSS version 25. The results showed that financial performance and firm size had a significant influence on firm value. However, the capital structure variable does not significantly affect the value of companies in the transportation and logistics sector that are listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period.